Glycaemic variability is associated with adverse cardiovascular outcomes in patients hospitalised with an acute myocardial infarction - Thora Y. Chai (Journal of Clinical & Translational Endocrinology, 2019)
Unlike admission hyperglycaemia, there is significant controversy surrounding whether acute glycaemic variability is associated with major adverse cardiovascular events (MACE) in patients immediately after an acute myocardial infarction (AMI). We conducted a retrospective post-hoc analysis in an AMI population and determined fluctuating glycaemia is associated with a higher risk of 3–month MACE. Keywords: Glycaemic variability, Mean amplitude of glucose excursion, Acute myocardial infarction, Major adverse cardiovascular events